2009
DOI: 10.1136/vr.164.3.91
|View full text |Cite
|
Sign up to set email alerts
|

Xanthinuria in a domestic shorthair cat

Abstract: | the VETERINARY RECORD SHORT COMMUNICATIONS catheter connected to a closed urine collection system. Routine blood work, including a complete blood count and serum chemistry profile, was unremarkable. Urinalysis revealed crystals suspected to be xanthine, and an inactive sediment. Plasma and 24-hour urine samples were submitted for xanthine and hypoxanthine measurements using HPLC and UV detection (Agilent 1000 series; Agilent Technologies), and 24-hour urine was submitted for uric acid measurements using a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 6 publications
2
19
0
Order By: Relevance
“…This report describes a young adult castrated DSH cat with xanthinuria similar to 5 previously described cats (White 1997; Tsuchida 2007; Schweighauser 2009; Mestrinho 2013). A diagnosis of hereditary xanthinuria was suspected based upon the urinary crystal morphology and confirmed by analyses showing calculinmade up of 100% xanthine together with high urinary xanthine values.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This report describes a young adult castrated DSH cat with xanthinuria similar to 5 previously described cats (White 1997; Tsuchida 2007; Schweighauser 2009; Mestrinho 2013). A diagnosis of hereditary xanthinuria was suspected based upon the urinary crystal morphology and confirmed by analyses showing calculinmade up of 100% xanthine together with high urinary xanthine values.…”
Section: Discussionsupporting
confidence: 64%
“…In cats, xanthinuria (Online Mendelian Inheritance in Animals 001283-9685) was previously described in 5 domestic shorthair (DSH) cats (White 1997; Schweighauser 2009; Mestrinho 2013) and 1 Himalayan cat (Tsuchida 2007). Laboratories dealing with urolith analysis reported that 0.1–0.3% of feline calculi analyzed were composed of xanthine (Osborne 2004; Canon 2007; Hesse 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is usually associated with the administration of allopurinol as part of the medical management for urate urolithiasis [6]. Naturally occurring xanthinuria has been reported only rarely in dogs, including a family of Cavalier King Charles [13] and Dachshunds [1,3], and in cats [9,12,15].…”
mentioning
confidence: 99%
“…Definitive diagnosis of naturally occurring xanthinuria based upon plasma and urine uric acid concentrations are characteristically very low, xanthine high and low or no activity of the enzyme XDH [2,9,15]. Another possibility to confirm the disease is to examine the family line: siblings, sire and the dam, but unfortunately the dam had been slaughtered one week prior the calf was euthanized, and there were no siblings.…”
mentioning
confidence: 99%
“…Uric acid: ­creatinine ratios in spot urine samples have been used to qualitatively identify hyperuricosuric dogs with a mutation of the urate transporter SLC2A9 (Karmi and others 2010) and these results were consistent with previous uric acid measurement via 24-hour urine collections (Bartges and others 1999). In a study of cats, concurrent xanthine and uric acid measurement in spot urine samples and 24-hour urine samples were positively correlated (Schweighauser and others 2009). …”
Section: Discussionmentioning
confidence: 99%